Lingkungan Pengendalian dan Moralitas Individu dalam Pencegahan Fraud yang Terjadi pada Pengelolaan Alokasi Dana Desa - Siska Nur; Zikra Supri; Riyanti Riyanti (Owner : Riset dan Jurnal Akuntansi, 2023)
Fraud is an illegal act that is carried out by a person or more than one person, either intentionally or unintentionally, to gain profit in various ways to obtain money, assets and so on which can harm many parties. This study aims to determine whether the control environment and individual morality influence the prevention of fraud that occurs in the management of Village Fund Allocations (ADD), and to add insight into fraud in Indonesia, especially in remote villages. The samples in this study were village officials, village consultative bodies (BPD) in Bonelemo Barat Village, Saronda Village, Tumbubara Village, Tetekang Village, Marinding Village. West Bajo district in Luwu district. The data is collected by using a questionnaire with a Likert scale. This research includes descriptive research with a quantitative approach. The analytical tool for testing the hypothesis is multiplication linear regression analysis using the IBM Statistics SPSS 21 program. This variable indicates that the control environment has an effect on preventing fraud in the allocation of village funds in the West Bajo sub-district and morality has no effect on preventing fraud in the allocation of village funds.